Performance Analysis of the General Criminal Investigation Directorate in Revealing the Crime of Theft - Gita Puspita Masekan (Universitas Negeri Gorontalo, 2021)
Abstract: This study aims to determine the role of the general criminal directorate detective in uncovering the crime of car theft in the Acc Finance warehouse. This type of research uses empirical legal research with a qualitative approach. The results of this study indicate that the efforts made by the Gorontalo Regional Police, especially to prevent the occurrence of car theft crimes, the police conduct raids/control operations on motorized vehicle completeness (sweeping), especially cars on a regular basis in several locations that are known to be places that are prone to car theft crimes. , conduct counseling on the dangers of the crime of theft of motorized vehicles, especially cars, billboards advertising public services with an appeal to members of the public to be more careful in storing and or parking motorized vehicles, especially cars, in collaboration with the surrounding community to prevent crime. the crime of vehicle theft by giving an appeal so that community members remind the security system in their respective environments by means of preventive measures in the form of raids/operations by directly involving community members to further improve security and the environment. their territory by increasing the security system and the active role of community members in an effort to improve security in their respective environments.